Waterway continuous monitoring using fiber optic sensing system: article / Muhammad Ammar Afif Ahmad - Ahmad, Muhammad Ammar Afif (2014)
This project presents a waterway monitoring system using fiber optic sensing approach that can monitor certain parameters of water. The optical fiber based system can continuously monitor and alert the authorities if sudden changes in parameters happen. The problem with the existing system is that the system is either labour intensive or requires data connection. The objective of this project is to develop a continuously monitoring system that can detect the changes in parameters along waterway such as river which also will be focused throughout development of this project. The scope of work for this project are to design a system that cover long distance monitoring and allow detection of changes in different parameter such as oil detection, water level and pH of water. The methodology for this project is the information will be transmitted by light information through the optical fiber. The information will be fed to a detector that converts light to difference in voltage signal and optical analyzing tools that communicate to a PC and microcontroller. As a findings for this project, the functionality of this project can be illustrate by considering situation when there is change in parameters along the river such as changes of pH from pH 10 (alkaline) to pH 4 (acidic) ; the difference in output voltage signal of the electronic pH sensor will be converted into light signal and cause shifting of central wavelength. This information regarding the exact location of the situation will be sent to the authorities for further action. The benefit of this project is to ensure fast action from authorities in case any hazardous condition happens.